2021
DOI: 10.3389/fcimb.2021.707107
|View full text |Cite
|
Sign up to set email alerts
|

Sec62 Regulates Endoplasmic Reticulum Stress and Autophagy Balance to Affect Foot-and-Mouth Disease Virus Replication

Abstract: Endoplasmic reticulum (ER) stress-induced autophagy is closely associated with viral infection and propagation. However, the intrinsic link between ER stress, autophagy, and viral replication during foot-and-mouth disease virus (FMDV) infection is not fully elucidated. Our previous studies demonstrated that FMDV infection activated the ER stress-associated UPR of the PERK-eIF2a and ATF6 signaling pathway, whereas the IRE1a signaling was suppressed. We found that the activated-ATF6 pathway participated in FMDV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Nonetheless, there is evidence scattered throughout the literature that suggests that this could be not an isolated case and other viruses may hijack ER-phagy receptors. For example, the infection of foot-and-mouth disease virus (FMDV), a positive-strand RNA virus from the picornavirus family, triggers the expression of SEC62, which acts as an important antiviral factor by upregulating the IRE1-retinoic acid-inducible gene 1 (RIG-I)-dependent antiviral innate immune responses through an unknown mechanism, and FMDV evades this antiviral host defense mechanism by downregulating IRE1 levels ( 524 526 ). These observations may indicate that ER-phagy could be part of an immune response helping cells to cope with infections.…”
Section: Lysosomal Clearance Of the Er And Related Human Diseasesmentioning
confidence: 99%
“…Nonetheless, there is evidence scattered throughout the literature that suggests that this could be not an isolated case and other viruses may hijack ER-phagy receptors. For example, the infection of foot-and-mouth disease virus (FMDV), a positive-strand RNA virus from the picornavirus family, triggers the expression of SEC62, which acts as an important antiviral factor by upregulating the IRE1-retinoic acid-inducible gene 1 (RIG-I)-dependent antiviral innate immune responses through an unknown mechanism, and FMDV evades this antiviral host defense mechanism by downregulating IRE1 levels ( 524 526 ). These observations may indicate that ER-phagy could be part of an immune response helping cells to cope with infections.…”
Section: Lysosomal Clearance Of the Er And Related Human Diseasesmentioning
confidence: 99%
“…The rapid production of viral proteins by the ER induces ER stress and autophagy [82]. A recent study identified the Sec62 ER-phagy receptor as a key modulator of autophagic response during FMDV replication [83]. Depletion of Sec62 led to a significant increase in FMDV protein levels and viral titer.…”
Section: Other Rna Virusesmentioning
confidence: 99%
“…This effect was blocked by autophagy inhibitors, demonstrating that Sec62 facilitates ER-phagic degradation of viral proteins. FMDV appears to have evolved its own defense against this degradation: the investigators observed that levels of Sec62 in FMDV-infected cells decrease as infection continues, suggesting that the virus downregulates expression of Sec62 to preserve its replication process [83].…”
Section: Other Rna Virusesmentioning
confidence: 99%
“…In macrophages, the 2 C protein activates autophagy depending on WIPI1, WIPI2, ATG5, and ATG7, but not beclin-1 (Liao et al, 2013). Some controversial studies have also reported that autophagy is induced by FMDV infection through the PERK-eIF2a and ATF6 signaling pathways but has no effect on virus replication (Wu et al, 2021). The Seneca valley virus (SVV), another member of the Picornaviridae family, causes neonatal death and vesicular lesions in pigs (Hales et al, 2008).…”
Section: Increases Btv Replicationmentioning
confidence: 99%